ANALISIS KELAYAKAN FINANSIAL INDUSTRIALISASI RUMPUT LAUT ATC Chips DI TUJUH PROPINSI INDONESIA TIMUR - Susanto, Bambang; Sukadwilinda, Sukadwilinda (Jurnal Riset Akuntansi dan Keuangan, 2017)
Indonesia has one of the largest wet seaweed producer in the World. It will impact the economic value if the seaweed processing industry small and medium-scale can be established disentra seaweed production centers such as in Eastern Indonesia. The establishment of the seaweed industry small and medium-scale can be realized through several approaches, both economic and financial approach. The research method using descriptive analytic with field surveys as reinforcement data analysis . The object of this study is the financial analysis of the seaweed industry in Indonesia, especially in eastern regions such as South Sulawesi, Central Sulawesi, North Sulawesi, West Nusa Tenggara, East Nusa Tenggara, Maluku and North Maluku. The results of the financial analysis of the overall approach to demonstrate the positive zone seen from the feasibility, both NPV, IRR, and Payback Ratio ratio BC